FACTORS OF LOGISTICS AND FORWARDING SERVICE FORMATION AND DEVELOPMENT - Kucheruk, Galina; Bozhok, Anastasiia (Proceedings of National Aviation University (archive), 2016)
Purpose: Forwarding service is a key part of the system of goods movement and as such it provides realization of numerous services. Providing of new additional and unconventional services to cargo owners by haulers will extend the range of their clients, increase profits from sales, facilitate and accelerate the introduction of new transport technologies, increase stability and strength of relations in the transport market. Methods: We formulated requirements to be met by modern forwarding service. Carriage management should be based on logistics concept and its methods; comprehensive resource optimization of haulers and owners of cargo and other supply chain participants (insurance, financial ones, etc.). Optimization of the space-time chain, even involving freight forwarders (transport intermediaries), is a complex scientific and practical task. Results: We offer directions for development of forwarding additional and non-conventional service for forwarding system of cargo haulage service, which would also provide an opportunity to reduce transport time and increase service level. Discussion: A general scheme of products delivery to consumers contains a significant number of units-particular entities. It is important to analyze not only the position of economic entities in the market, but the features and capabilities of their interaction in major systemic tasks of forwarding service, quality and effective promotion of freight flows